MAIN DIRECTIONS OF ENSURING SAFETY CONDITIONS IN TOURISM - Botir Raxmatullaevich Pardaev (Web of Journals Publishing, 2025)
The article examines the main directions of security conditions in tourism. This work examines such issues as types of tourist problems, objects equipped with video surveillance cameras in Samarkand, indicators of safety of transport facilities, directions of information support in ensuring tourist security, main directions of investments in tourism security, as well as the creation of necessary conditions for the development of eco- and extreme tourism in the Samarkand region.
Keywords: Tourism security, tourist problems, tourist protection, tourist objects, tourist resources, information on security, environmental disasters, extreme tourism.